Covid-19, Unemployment, Effort to Tackle It - Damaianti, Indriana; Chaerudin, Ruli Mochammad (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The significant increase in Covid-19 cases illustrates the economic condition of the community and has an impact on the high unemployment rate. Object of study is economic growth, inflation, and unemployment rate. The type of study is an associative quantitative approach that aims to determine the effect of economic growth and inflation on the unemployment rate in West Java Province in 2015-2020. Data collection was obtained from secondary data taken from the Statictics Indonesia (BPS) of West Java Province. Technical analysis of the data used is multiple regression analysis using SPSS version 25.0 program. The results showed that economic growth affects the unemployment rate in West Java, while inflation does not affect it. The government must make the right policies and focus more on the stimulus for handling the pandemic going forward.